Kepemimpinan Biaya Yang Mengispirasi : Inovasi Multikultural Dalam Pendidikan Dan Optimalsasi Rantai Nilai - Eko Prayitno (CV. Amerta Media, 2024)
The current education management of Madrasah Ibtidaiyyah has not been able to play a role in preparing the expected graduates. This situation occurs because Madrasah Ibtidaiyyah (MI) does not know what innovations will produce graduates who are professional and can be an example for the ubudiyah and tolerant of differences. This research aims to explore madrasah educational activities in developing local and national content from the perspective of the value chain in achieving multicultural-based educational innovation. This research uses qualitative methods, with a case study approach. This research takes MI Raden Rahmat Mangunan Kabuh, Jombang as the object. Value chain activities implemented in the school provide extra value in the development of local and national content. Cost leadership implemented by the school succeeded in creating 1) quality-based education services at affordable costs, 2) community satisfaction with the motto